Platelet Rich Plasma in Medicine Basic Aspects and Clinical Applications - Ferneini, Elie M.; Landesberg, Regina; Halepas, Steven; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers a comprehensive overview of the use of platelet rich plasma (PRP), typically by injection, and its usage across medical disciplines. This multi-authored, multi-institutional, and multi-specialty based text is designed to guide health care providers in the varied uses of PRP -- starting from its history and preparation and moving through a variety of disciplines to illustrate how PRP can help healing. Clinical Applications of Platelet Rich Plasma in Medicine is divided into three sections: The first gives an overview of the basic science of PRP; the second provides a detailed overview of the clinical indications of PRP; and the third section discusses potential complications in conjunction with relevant case studies. It will feature a wealth of images and diagrams to illustrate best practices in using PRP. Written to be used by oral and maxillofacial surgeons, plastic surgeons, cosmetic surgeons, otolaryngologists, dentists, orthopedic surgeons, and general surgeons to name a few, this book will provide an evidence-based approach to using PRP in practice. The editors have extensive academic experience and have authored multiple scientific publications, while the contributions included in the text have been written by experts and leaders in the fields touched upon in the book.
Section I: Basic Science of PRP -- 1. History of PRP -- 2. PRP Science -- 3. PRP Preparation -- 4. PRF vs. PRP -- Section II: Clinical Applications of PRP -- 5. PRP in Sports Medicine -- 6. PPR in Wound healing -- 7. PRP in Hair restoration -- 8. PRP in Facial Rejuvenation -- 9. PRP in Oral Surgery -- 10. PRP in Dental Implants -- 11. PRP with bone grafting/periodontal surgery -- 12. PRP in Veterinary Medicine -- 13. Stem cell and PRP -- Section III: Complications and Relevant Cases -- 14. Complications -- 15. Cases.
Keywords: Surgery; Surgery; Surgery; Platelet-Rich Plasma; Medicine